Academics’ concern on graduate employability amidst the pandemic / Faizah Abd. Majid, Wan Nurul Elia Haslee Sharil and Mohd Alif Amin Salmee - Abd Majid, Faizah; Sharil, Wan Nurul Elia Haslee; Salmee, Mohd Alif Amin (Universiti Teknologi MARA, 2022)
This article was written as part of a bigger research project on developing a Graduate Employability (GE) Teaching Model which received university funding. Recent years have seen a growing literature on GE. The need for soft skills training is seen as parallel with the need to enhance employability skills. The changing work landscape due to the VUCA (volatile, uncertainty, complex and ambiguous) world suggests a higher demand for the concerns on graduate employability and employability skills to be addressed. Needless to say, the pandemic brought with it a force that challenged the norm in how higher education is provided and brought an amplified concern on how GE is addressed during the pandemic. As part of the bigger data collection procedure, a focus group interview based on a semi-structured interview protocol was conducted as an attempt to uncover how academics train their students’ GE skills. The investigation rested on several key issues; their approach in developing GE skills, the critical issues faced while developing the GE skills and the support they require in developing GE skills among their students. At the onset of the study, the context of the pandemic guided the direction of the data collection and analysis. The report from this small-scale study provided initial findings that could be referred to as the research progressed into further data collection via the mixed method research design. The qualitative data from the interview was analysed based on themes and sub-themes as guided by the research questions and the interpretations were supported by relevant literature. Interesting findings were yielded from the the analysis suggesting potential preliminary findings that could be referred to in an attempt to develop a teaching model for GE. Besides the policy makers and curriculum developers, future researchers may find this article as an important reference in their work.